Effect of Blending Ratio on Temperature Profile and Syngas Composition of Woody Biomass Co-gasification - Shaharin Anwar, Sulaiman; M., Inayat; H., Basri; F. M., Guangul; Atnaw, Samson M. (Penerbit UMP, 2016)

(untitled)
Co-gasification of biomass is beneficial as only relying on one type of biomass causes interruption in gasification if the feedstock supply is disrupted for any reason. Therefore, co-gasification of different biomass materials is a potential way to overcome the problem. In this work, co-gasification of wood chips (WC) and coconut fronds (CF) was carried out in a downdraft gasifier at 400 L/min airflow rate. Three blends of WC/CF of 70:30, 50:50 and 30:70 ratios were considered with a maximum particle size of 2.5-3.0 cm. The aim of this study was to investigate the effect of blending ratio on the temperature profile and syngas composition produced by the co-gasification of WC/CF blended feedstock. The results show that the temperature profile and syngas composition of 70:30 WC/CF blend was comparatively better. The average syngas composition of 70:30 WC/CF blend during steady state co-gasification operation was 20%, 12% and 3% for CO, H2 and CH4 respectively. Similarly, the average syngas composition of 50:50 WC/CF blend was around 21%, 8% and 0.7% for CO, H2, and CH4 respectively. While the 30:70 WC/CF blend encountered with bridging problem due to fibrous and low density CF. No more than 50% of fibrous and low density feedstock like CF is recommended in a blend for stable and progressive co-gasification.